Lexical archaism in some Kabyle proverbs: a lexico-semantic analysis: تحليل استراتيجيات ترجمة الاستعارة إلى العربية في رواية جورج أورويل "1984" - Ferguenis , Lyes (Maalim, 2026)
The main objective of this study is to identify lexical archaisms present in several Kabyle proverbs and to compare them according to their degree of archaization. This comparison will focus on the two regions where we conducted our fieldwork. To achieve this objective, we relied on fieldwork, as it allowed us to meet our informants directly. Our research methodology is based on direct interviews, which enabled us to compile our corpus and gather the information necessary for our study (particularly the identified archaisms and their meanings). Our corpus consists of proverbs collected in the Iẓnagen and Amizour regions. This corpus underwent a lexico-semantic analysis. The results we obtained show that the phenomenon of archaism is particularly complex: the differences between regions can concern the word itself, its degree of archaization, or its meaning. Therefore, further research of this type, focusing on other proverbs and/or other regions, would be necessary. Such research would contribute to the development of the language, particularly in the fields of lexicology and lexicography.